Tafsir Tarbawi as the Foundation for Humanist Education in Islam - Ach. Muqoddas; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
This research examines the role of Tafsir Tarbawi as the foundation of humanist education in Islam with a focus on Surah Al-Anfal verse 61. This verse emphasizes the importance of peace even in conflict situations, which can be used as a basic principle in the development of an Islamic education system that is oriented towards human values. The methodology used in this research is library study (library research), by analyzing various literature related to Tarbawi Tafsir, interpretation of verses from the Koran, and the concept of humanist Islamic education. The research results show that Tafsir Tarbawi can provide a deep perspective on how this verse can be applied in building students' character based on peace, tolerance and mutual understanding. Based on Asbabun Nuzul Al-Quran Surah Al-Anfal (8:61), Tafsir Wajiz, Tafsir Tahlili, Meaning of the Verses this research also highlights the relevance of applying these principles in the Islamic education curriculum to create a generation that is responsible and has noble character. It is hoped that the results of this research can make a significant contribution to the development of Islamic education that is more humanistic and in accordance with the demands of the times.